Consuming Cities - Elander, Ingemar (Taylor & Francis, 2000)
This book is about cities as engines of consumption of the world's environment, and the spread of policies to reduce their impact. It looks at these issues by examining the impact of the Rio Declaration and assesses the extent to which it has made a difference. Consuming Cities examines this impact using case studies from around the world including: the USA, Japan, Germany, the UK, China, India, Sweden, Poland, Australia and Indonesia The contributors all have direct experience of the urban environment and urban policies in the countries on which they write and offer an authoritative commentary which brings the urban 'consumption' dimension of sustainable development into focus.